YOLO — Your own living object - Alves-Oliveira, P.; Arriaga, P.; Paiva, A.; Hoffman,G. (Companion of the 2020 ACM/IEEE International Conference on Human-Robot Interaction (HRI ’20 Companion), 2020)
Creativity is at the core of what it means to be human. It is an intrinsic ability that we all have and influences our well-being self-expression throughout life. However, a decline in creativity abilities occurs in children around the age of 7 years old. Our work aims to contribute to a re-balance of creative levels using social robots. In this video, we describe YOLO, an autonomous robotic toy for children that fosters their creativity during play. This robot is envisioned to be used as a character during storytelling, promoting creative story-lines that might not emerge otherwise.